Spatial–temporal pattern of propagation in amyotrophic lateral sclerosis and effect on survival: A cohort study. (9th September 2022) - Yang, Tianmi; Wei, Qianqian; Li, Chunyu; Cao, Bei; Ou, Ruwei; Hou, Yanbing; Zhang, Lingyu; Gu, Xiaojing; Liu, Kuncheng; Lin, Junyu; Cheng, Yangfan; Jiang, Zheng; et al.
Abstract: Background and purpose: Clarification of propagation patterns in amyotrophic lateral sclerosis (ALS) is challenging, but understanding these has implications for individual prognostication and clinical trial design. However, systematic knowledge in this area is lacking. The aim of this study was to characterize the spatial and temporal features of propagation patterns in ALS, and to evaluate the association between propagation patterns and survival. Methods: A cohort of 833 patients with ALS, diagnosed between January 2018 and December 2019 and followed to August 2021, was analysed. Spatial and temporal features of propagation patterns were determined based on the involved functional regions (bulbar, cervical, thoracic/respiratory and lumbar) in time order. The final propagation pattern was identified in patients with at least three functional regions involved. Kaplan–Meier analysis and Cox regression analysis were performed. Results: During a median follow‐up of 21.2 months, 19 final propagation patterns were identified in 657 patients (78.9%). In survival analysis, we found that the earlier the respiratory functional region becomes involved, the higher the risk of death (time order: 1st: hazard ratio [HR], 3.35, 95% confidence interval [CI] 1.23–9.15; 2nd: HR 2.45, 95% CI 1.55–3.87; 3rd: HR 1.94, 95% CI 1.52–2.49), adjusting for age, sex, diagnostic delay, revised ALS Functional Rating Scale score, cognitive impairment and riluzole. Shorter interval time between involved regions was an independent adverse prognostic factor. Conclusions: The propagation patterns of ALS are varied. The order in which the respiratory region becomes involved and the interval time between involvement of functional regions are predictors for prognosis.